Hydrogeochemical Peculiarities of the Composition of Nitric Thermal Waters in the Baikal Rift Zone; Russian Geology and Geophysics; Vol. 54, iss. 5 - Plyusnin A. M.; Zamana L. V.; Shvartsev S. L. Stepan Lvovich; Tokarenko O. G. Olga Grigorievna; Chernyavskii M. K. (2013, 2013)
Title screen